Studi in silico senyawa Echinochrome-A, Spinochrome-A, and Echinamine-A pada Echinometra mathaei dalam menghambat enzim maltase-glucoamylase sebagai antidiabetes - Prasetyanti, Intan; Kresnamurti, Angelica (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
DM can be caused by the release and absorption of glucose in the small intestine by digestive enzymes. Inhibition of this enzyme can help manage DM. Human Maltase-glucoamylase (MGA) is an enzyme in the small intestine that is responsible for catalyzing the release of glucose from carbohydrate digestion. By inhibiting this enzyme, it is hoped that glucose in type 2 diabetes patients can be controlled. Analyze the potential of Echinochrome-A, Spinochrome-A, and Echinamine-A in Echinometra mathaei extract as an antidiabetic using molecular docking. Molecular docking using Echinochrome-A, Spinochrome-A, Echinamine-A as a compound test and Miglitol as standard for the Human Maltase-glucoamylase receptor. Echinochrome-A, Spinochrome-A, and Echinamine-A has an affinity and hidrogen bonds with amino acid residues that are not significantly different from Miglitol, so that Echinochrome-A, Spinochrome-A, and Echinamine-A has potential as an antidiabetic.